Environmental Mycobacterium avium subsp. paratuberculosis Hosted by Free-Living Amoebae - Samba-Louaka, Ascel; Robino, Etienne; Cochard, Thierry; Branger, Maxime; Delafont, Vincent; Aucher, Willy; Wambeke, Wilfrid; Bannantine, John P.; Biet, Franck; Héchard, Yann (Frontiers in Cellular and Infection Microbiology, 2018)
Mycobacterium avium subsp. paratuberculosis is responsible for paratuberculosis in animals. This disease, leading to an inflammation of the gastrointestinal tract, has a high impact on animal health and an important economic burden. The environmental life cycle of Mycobacterium avium subsp. paratuberculosis is poorly understood and several studies suggest that free-living amoebae might be a potential environmental host. Free-living amoebae are protozoa found in water and soil that are described as reservoirs of pathogenic bacteria in the environment. Indeed, bacteria able to survive within these amoebae would survive phagocytosis from immune cells. In this study, we assessed the in vitro interactions between several strains of Mycobacterium avium subsp. paratuberculosis and Acanthamoeba castellanii. The results indicate that the bacteria were able to grow within the amoeba and that they can survive for several days within their host. To explore the presence of Mycobacterium avium subsp. paratuberculosis in environmental amoebae, we sampled water from farms positive for paratuberculosis. A Mycobacterium avium subsp. paratuberculosis strain was detected within an environmental amoeba identified as related to the poorly described Rosculus genus. The bacterial strain was genotyped, showing that it was similar to previous infectious strains isolated from cattle. In conclusion, we described that various Mycobacterium avium subsp. paratuberculosis strains were able to grow within amoebae and that these bacteria could be found on farm within amoebae isolated from the cattle environment. It validates that infected amoebae might be a reservoir and vector for the transmission of Mycobacterium avium subsp. paratuberculosis.